Enhancing the Microstructure of Perovskite-Inspired Cu-Ag-Bi-I Absorber for Efficient Indoor Photovoltaics - Grandhi G. Krishnamurthy; Al-Anesi Basheer; Pasanen Hannu; Ali-Löytty Harri; Lahtonen Kimmo; Granroth Sari; Christian Nino; Matuhina Anastasia; Liu Maning; Berdin Alex; Pecunia Vincenzo; Vivo Paola (WILEY-V C H VERLAG GMBH, 2022)
Lead-free perovskite-inspired materials (PIMs) are gaining attention in optoelectronics due to their low toxicity and inherent air stability. Their wide bandgaps (≈2 eV) make them ideal for indoor light harvesting. However, the investigation of PIMs for indoor photovoltaics (IPVs) is still in its infancy. Herein, the IPV potential of a quaternary PIM, Cu2AgBiI6 (CABI), is demonstrated upon controlling the film crystallization dynamics via additive engineering. The addition of 1.5 vol% hydroiodic acid (HI) leads to films with improved surface coverage and large crystalline domains. The morphologically-enhanced CABI+HI absorber leads to photovoltaic cells with a power conversion efficiency of 1.3% under 1 sun illumination-the highest efficiency ever reported for CABI cells and of 4.7% under indoor white light-emitting diode lighting-that is, within the same range of commercial IPVs. This work highlights the great potential of CABI for IPVs and paves the way for future performance improvements through effective passivation strategies.